Inkjet Printing of Flexible Transparent Conductive Films with Silver Nanowires Ink - Xiaoli Wu; Shuyue Wang; Zhengwu Luo; Jiaxin Lu; Kaiwen Lin; Hui Xie; Yuehui Wang; Jing-Ze Li (Nanomaterials, 2021)
The inkjet printing process is a promising electronic printing technique for large-scale, printed, flexible and stretchable electronics because of features such as its high manufacturing speed, environmental friendliness, simple process, low cost, accurate positioning, and so on. As the base material of printed conductive patterns, conductive ink is the foundation of the development of printed electronics technology, and directly affects the performance and the quality of electronic products. In this paper, conductive ink with silver nanowires (AgNWs) was prepared, with AgNWs of lengths of 2–5 µm and diameters of 20 nm or so, isopropyl alcohol and ethylene glycol as the mixed solvents, and modified polysilane as the wetting agent. We discussed the relationship between the formula of the AgNWs ink and the surface tension, viscosity, contact angle between ink droplet and poly(ethylene) terephthalate (PET) surface, as well as the film-forming properties of the ink. Further, we analyzed the effects of the number of printed layers and the ink concentration of the AgNWs on the microstructures, photoelectric properties and accuracy of the printed patterns, as well as the change in the sheet resistance of the film during different bending cycles. The experimental results show that flexible transparent conductive patterns with a light transmittance of 550 nm of 83.1–88.4% and a sheet resistance of 34.0 Ω∙sq−1–78.3 nm∙sq−1 can be obtained by using AgNWs ink of 0.38 mg∙mL−1 to 0.57 mg∙mL−1, a poly (ethylene terephthalate) (PET) substrate temperature of 40 °C, a nozzle temperature of 35 °C, and heat treated at 60 °C for 10 min. These performances indicate the excellent potential of the inkjet printing of AgNWs networks for developing flexible transparent conductive film.